Growth substrate effects on acetate and methanol catabolism in Methanosarcina sp. strain TM-1. - Zinder, S H (1985)
When Methanosarcina sp. strain TM-1 is grown in medium in which both methanol and acetate are present, growth is biphasic, with methanol used as the primary catabolic substrate during the first phase. To better understand this phenomenon, we grew cells on methanol or on acetate or on both and examined the abilities of anaerobically washed cells to catabolize these substrates. Washed acetate-grown cells incubated with 10 mM acetate, 10 mM methanol, or both substrates together produced methane at initial rates of 325, 3, and 315 nmol min-1 mg of protein-1, respectively. Although the initial rate of methanogenesis from both substrates was nearly identical to the rate for acetate alone, after several hours of incubation the rate was greater for cells provided with both substrates. Studies with 14C-labeled methanol indicated that methanol was catabolized to methane at increasing rates by acetate-grown cells in a manner reminiscent of an induction curve, but only when cells were provided with acetate as a cosubstrate. Acetate was presumably providing energy and carbon for induction of methanol-catabolic enzymes. Methanol-grown cells showed a pattern of substrate utilization significantly different from that of acetate-grown cells, producing methane from 10 mM acetate, 10 mM methanol, or both substrates at initial rates of 10, 280, and 450 nmol min-1 mg of protein-1, respectively. There was significant oxidation of the methyl group of acetate during metabolism of both substrates. Cells grown on methanol-acetate and harvested before methanol depletion (methanol phase) showed catabolic patterns nearly identical to those of methanol-grown cells, including a low rate of methanogenesis from acetate. Cells harvested from methanol-acetate cultures in the acetate phase were capable of significant methanogenesis from either methanol or acetate alone, and the rate from both substrates together was nearly equal to the sum of the rates for the single substrates. When both 10 mM methanol and 10 mM acetate were presented to the acetate-phase cells, there was a preference for the methanol. These results are consistent with a model for regulation in Methanosarcina sp. strain TM-1 in which methanol represses acetate catabolism while methanol catabolism is inducible.